Survival of patients with chronic myeloproliferative neoplasms and new primary cancers: a population-based cohort study. Issue 7 (July 2015) - Frederiksen, Henrik; Farkas, Dóra Körmendiné; Christiansen, Christian Fynbo; Larsen, Thomas Stauffer; Hasselbalch, Hans Carl; Stentoft, Jesper; Sørensen, Henrik Toft
Summary: Background: Patients with chronic myeloproliferative neoplasms are at increased risk of new solid or haematological cancers, but how prognosis is affected in patients with preceding myeloproliferative neoplasms is unclear. Methods: We used data from population-based medical databases in Denmark from 1980 to 2011 to compare survival between cancer patients with and without a preceding diagnosis of myeloproliferative neoplasm, matched for age, sex, year of diagnosis, and type of cancer. We assessed outcomes by cancer stage and comorbidities. Findings: Data were available for 1246 patients with a history of myeloproliferative neoplasms and we matched 5155 patients without a history of myeloproliferative neoplasm for comparison. Among patients with new localised solid cancers, 5-year survival was 49·8% (95% CI 39·1–59·6) for patients with preceding essential thrombocythaemia, 47·9% (42·1–53·4) for those with preceding polycythaemia vera, and 48·0% (34·1–60·7) for those with preceding chronic myeloid leukaemia. The values were 72·4% (68·4–76·0), 63·9% (61·5–66·2), and 74·3% (68·2–79·4), respectively, in matched patients without preceding myeloproliferative neoplasms. The risk of death among patients with a solid tumour and preceding myeloproliferative neoplasm was 1·21–2·28 times higher than in patients without myeloproliferative neoplasms. Excess mortality risk was observed irrespective of whether new cancers were diagnosed within 5 years or 5 years or more after myeloproliferative neoplasm. Interpretation: Preceding myeloproliferative neoplasm is a predictor for poor outlook in patients who develop new primary cancers. Funding: Lundbeck and Novo Nordisk Foundation Programme for Clinical Research Infrastructure, Danish Cancer Society, and Aarhus University Research Foundation.